#TITLE_ALTERNATIVE# - RAMADHANI SYAHPUTRA (NIM 12103023); Pembimbing : Dr. Ir. Budi Sulistianto, MT., ERICK
The biggest investment in mining operation is equipment. Therefore, it needs analysis of parameters that influence the production of mechanical equipment in order to use it effectively and efficiently. An effort to increase production in this research was analyzed by optimizing the number of truck based on a match factor that has been considered the suitable capacity of bucket excavator and truck. More over, the efforts were also performed by simulating the parameters that affect production such as loading method, bucket fill factor and the equpment availability. In this research, it was revealed that amount of trucks at loading point area of RH 200 (7001), RH 200 (7002), RH 340 (7003), RH 340 (7004), RH 340 (7005), Hitachi Ex 5500 (7006), and Hitachi Ex 5500 (7007) are 4 Terex units, 5 Terex units, 5 Liebherr units, 4 Liebherr units and 2 Komatsu units, 6 Liebherr units, 6 Komatsu units, and 7 Komatsu units, respectively. This could increase total production from 7390 bcm/hour to 7583 bcm/hour, which equal to 2,61 % increasing. Based on the simulation analysis, the optimal amount of trucks at loading point area of RH 200 (7001), RH 200 (7002), RH 340 (7003), RH 340 (7004), RH 340 (7005), Hitachi Ex 5500 (7006), and Hitachi Ex 5500 (7007) are 6 Terex units, 7 Liebherr units, 6 Terex units, 7 Liebherr units, 8 Liebherr units, 7 Komatsu units, and 8 Komatsu units, respectively. This could increase total production from 7390 bcm/hour to 9518 bcm/hour, which equal to 28,79 % increasing.